An Analysis of Japanese Rituals of A new Geisha in Arthur Golden's Novel Memoirs of A Geisha - Rachmayanti, Eva; Andini, Thathit (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis of Japanese Rituals of A new Geisha in Arthur Golden's Novel Memoirs of A Geisha